The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3847/1538-4357/acac81
|View full text |Cite
|
Sign up to set email alerts
|

JCMT BISTRO Observations: Magnetic Field Morphology of Bubbles Associated with NGC 6334

Abstract: We study the Hii regions associated with the NGC 6334 molecular cloud observed in the submillimeter and taken as part of the B-fields In STar-forming Region Observations Survey. In particular, we investigate the polarization patterns and magnetic field morphologies associated with these Hii regions. Through polarization pattern and pressure calculation analyses, several of these bubbles indicate that the gas and magnetic field lines have been pushed away from the bubble, toward an almost tangential (to the bub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 120 publications
(171 reference statements)
0
3
0
Order By: Relevance
“…While we adapted this decomposition and applied it to the B-fields of spiral galaxies, our method can also be applied to any vector field where a circle or ellipse is a geometry of particular interest. Apart from galaxies, this method could also be adapted to other ISM morphologies, such as supernova remnants or windblown bubbles in star-forming regions (e.g., Tahani et al 2023), or radio synchrotron loops (e.g., Vidal et al 2015).…”
Section: Broader Applicationsmentioning
confidence: 99%
“…While we adapted this decomposition and applied it to the B-fields of spiral galaxies, our method can also be applied to any vector field where a circle or ellipse is a geometry of particular interest. Apart from galaxies, this method could also be adapted to other ISM morphologies, such as supernova remnants or windblown bubbles in star-forming regions (e.g., Tahani et al 2023), or radio synchrotron loops (e.g., Vidal et al 2015).…”
Section: Broader Applicationsmentioning
confidence: 99%
“…as defined by Tahani et al (2023) and shown in Figure 3 for the HAWC+ 53 μm (upper left panel), HAWC+ 154 μm (upper right panel), and the JCMT POL-2 850 μm observations (lower panel). The data have the same constraints of S/N(I) > 20 and S/N(P) > 2.5.…”
Section: Radial Coordinate Polarizationmentioning
confidence: 99%
“…Therefore, magnetic fields are believed to introduce anisotropy in the gas motion and consequently have a significant impact on structure formation and evolution in the ISM, ranging from galaxy formation to the formation of filamentary molecular clouds within a single star-forming region (Heiles & Crutcher 2005;Boulanger et al 2018). Indeed, magnetic field lines are expected to be influenced by the motion of the ISM, leading to their dragging or bending (e.g., Doi et al 2021a;Tahani 2022;Tahani et al 2023). As a result, the interstellar magnetic field structure is expected to be inscribed with a history of the deformation of the ISM (Gómez et al 2018).…”
Section: Introductionmentioning
confidence: 99%